Penerapan Regresi Robust pada Pengeluaran Listrik Rumah Tangga Miskin di Perkotaan dan Perdesaan Kawasan Timur Indonesia Tahun 2020 - Vina Tri Yasmi; Lia Yuliana (Politeknik Statistika STIS, 2021)
The Eastern Region of Indonesia (EI) has a lower electrification ratio than the Western Region of Indonesia. This means that there are more households in EI that do not have access to electricity which is also in line with the high percentage of poverty in EI. The percentage of poverty in rural areas is also higher and access to electricity is more difficult than in urban areas. The electricity subsidy budget targeting poor households also continues to increase even though the targeted subsidy policy was implemented in 2017. Therefore, this study aims to determine the socio-economic characteristics and electricity consumption of poor households in urban and rural EI in 2020, as well as analyze socio-economic characteristics that affect the electricity expenditure of poor households in urban and rural EI in 2020. The results with robust regression indicate that the variables that had a positive significant effect on the electricity expenditure of poor households in urban and rural areas are higher education of household head, number of household members, floor area, income per capita, electronic ownership, and the significant negative is residence ownership. The secondary education of household head are only significant in rural areas, while those that are not significant in urban and rural areas are the age of household head and working activity of household head.